Islamic Education and the Principles of Social Justice: Implications for Government Responsibilities in Providing Compensation and Restitution - Hamamah, Fatin (Letiges, 2023)
The principle of legal equality, one of the fundamental principles in the rule of law, emphasizes the importance of providing legal protection to victims in the criminal justice process. This study examines existing compensation and restitution arrangements from an Islamic education studies perspective. This is important to strengthen the values of social justice, which are reflected in the Islamic education approach, which prioritizes the protection of victims as a moral and religious ethical mandate. This study will use a qualitative research method with a normative system based on Pancasila's philosophy from the Islamic education perspective. This research will collect quality data through interviews, observation, and document analysis, which will be analyzed inductively. The results of this study indicate that compensation and restitution arrangements in positive law still need to reflect the principles of justice recommended in Islam. From the perspective of Islamic education, this study highlights the need for legal policies based on Islamic values in implementing restitution for victims of criminal acts, taking into account human values, justice and social responsibility. The importance of harmonising legal substance and structure in an integrated criminal justice system was also found. In conclusion, improvements are needed in compensation and restitution arrangements so that they pay attention to victims of crime and are by the values and legal culture of the society in the perspective of Islamic education, with the government's responsibility to maintain the balance of the rights of perpetrators and victims in the criminal justice system.